102k views
19 votes
My first expression answer is y=5 -2x How do I plug it into x-y=1 ?? The Y

1. x-5-2x=1 OR

2. x+5-2x=1

1 Answer

10 votes

Answer:

All you need to do is make sure the first expression is solved for y (which it is), and then substitute it into the second expression in place of any occurrences of y:

given the second expression:

x - y = 1

We'll replace y with it's value in the first expression:

x - (y) = 1

x - (5 - 2x) = 1

Now we can expand the resulting equation:

x - 5 + 2x = 1

So neither of the answers provided are correct.

You can then solve for x:

x - 5 + 2x = 1

x - 5 + 5 + 2x = 1 + 5

x + 2x = 6

3x = 6

3x/3 = 6/3

x = 2

After that, you can find y by plugging x into either of the two original equations:

y = 5 - 2x

y = 5 - 2(2)

y = 5 - 4

y = 1

User Hvtilborg
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.